Can there be a Catholic approach to the teaching of physics to students in Catholic universities? Some ideas for teachers and students to consider. Issue 2 (3rd July 2019) - Canetta, Elisabetta
Abstract : We currently live in a high-tech society where portable supercomputers, artificial intelligence, genetic enhancement, etc., are becoming part of our daily life. It can be argued that this steady flow of complex technology is vigorously pushing aside religion and faith in God. Nowadays if a student decides to study physics he/she cannot possibly think of, nor have an interest in philosophy, let alone theology. This limited attitude towards physics is stripping it of its real meaning and purpose. This paper argues that physics is a study that God has put in the hands of humanity to be used in conjunction with philosophy and theology, in order not only to be able to ask big questions about nature and the universe, but also to actively contribute to finding some answers to them. Ideas about a scientific-philosophical-theological approach to teaching physics at the undergraduate level within a Catholic institution are presented and discussed.